The double-edged sword effect of warming on the soil predatory mite Cosmolaelaps brevistilis (Karg, 1978) (Mesostigmata: Laelapidae) - Barroso, Geovanny; Barreto, Carlos; Padilha, Aline C.; Pazini, Juliano B.; Santos, Jandir C.; Godoy, Lucas L.; Yamamoto, Pedro T. (Entomological Communications, 2023)
In this study we used the average annual temperature in Brazil and four warming predictions to propose a maximum thermal threshold for the predatory mite Cosmolaelaps brevistilis (Karg, 1978) (Mesostigmata: Laelapidae) as an experimental model. Then, we evaluated the effects of warming on the biological parameters of C. brevistilis for conservation biological control. We observed higher rates of oviposition and predation of the prey Tyrophagus putrescentiae (Schrank, 1781) (Astigmatina: Acaridae) under warmer conditions at 75 ± 10% RH. The highest rates of prey consumption and oviposition were observed at 28°C compared to the others tested (22, 24, and 26°C). However, the egg viability of C. brevistilis was reduced at the same temperature. Therefore, temperature increases both positive and negative effects on the biological parameters of C. brevistilis which are important for the ecological interactions that are essential for biological control programs.